Neuromyelitis optica antibody in Leber hereditary optic neuropathy: case report - Simão,Luciano Mesquita (2012)
Neuromyelitis optica antibody (or aquaporin-4 antibody) is a well stablished serum marker associated to high-risk neuromyelitis optica syndrome that presents as an inflammatory demyelinating disease characterized by the occurrence of bilateral and simultaneous optic neuritis without complete visual recovery or it occurs as an isolated episode of transverse myelitis accompanied by longitudinally extensive spinal cord lesions. On the other hand, Leber hereditary optic neuropathy is a primarily hereditary disorder that affects all tissues of the body and its clinical presentation is tissue-specific for the optic nerve and, eventually, it might reach the spinal cord. Overlapping clinical features of neuromyelitis optica and Leber hereditary optic neuropathy may suggest common target organ diseases. The case report described herein emphasizes the coexistence of serum markers of both diseases, and suggests that further investigation of this challenging clinical presentation is warranted to confirm or rule out this association.